Beyond corporate social responsibility: Strengthening human rights due diligence through the legally binding instrument on business and human rights - Daniel Uribe Terán (South Centre, 2021)
The discussion on the need for mandatory human rights due diligence (HRDD) requirements has permeated the interests of policy makers, civil society organizations and international organizations. The current trend on the adoption of domestic legislation concerning HRDD standards shows a variety of options and models that might serve as a step forward to the adoption of a strong international framework of corporate accountability and remedy for human rights violations in the context of business activities. This research paper aims at identifying the elements that characterize human rights due diligence to find a possible common definition for its implementation. It does so through analysing current regional and State practice in the adoption of mandatory HRDD legislation in different sectors. Finally, it will discuss the principles that characterize the approach taken by the United Nations Open-ended Intergovernmental Working Group in charge of adopting a Legally Binding Instrument on transnational corporations and other business enterprises and how it could serve as an important cornerstone for modern rule making on the issue of business and human rights.
Keywords: 300